2022
DOI: 10.3390/jcm11082073
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in Dacryoendoscopic Visibility after Image Processing Using Comb-Removal and Image-Sharpening Algorithms

Abstract: Recently, a minimally invasive treatment for lacrimal passage diseases was developed using dacryoendoscopy. Good visibility of the lacrimal passage is important for examination and treatment. This study aimed to investigate whether image processing can improve the dacryoendoscopic visibility using comb-removal and image-sharpening algorithms. We processed 20 dacryoendoscopic images (original images) using comb-removal and image-sharpening algorithms. Overall, 40 images (20 original and 20 post-processing) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…The honeycomb-removal technology was originally developed for improving the imaging quality of endoscopes for other organs, such as gastrointestinal endoscopes, which was then applied to dacryoendoscopes [ 8 , 9 ]. The noise caused by the honeycomb structure appears as a high-frequency component in the spatial frequency domain and can be removed by a low-pass filter.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The honeycomb-removal technology was originally developed for improving the imaging quality of endoscopes for other organs, such as gastrointestinal endoscopes, which was then applied to dacryoendoscopes [ 8 , 9 ]. The noise caused by the honeycomb structure appears as a high-frequency component in the spatial frequency domain and can be removed by a low-pass filter.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, new technologies have been developed and implemented to improve the live endoscopic images by honeycomb-removal and image-sharpening algorithms with a delay of 0.004 s [ 8 ]. Clinical and experimental studies demonstrated that application of such image-processing procedures could improve dacryoendoscopic visibility and thus potentially increase the diagnostic accuracy and treatment outcomes in patients with lacrimal passage obstruction [ 8 ]. We conducted the current study to assess whether honeycomb-removal and image-sharpening algorithms can increase the visibility in small-gauge endoscopic vitrectomy.…”
Section: Introductionmentioning
confidence: 99%
“…In Northeast Asia, endoscopic-assisted nasolacrimal duct intubation (ENDI) has been proposed as an alternative to DCR for the treatment of postsaccal obstruction. This is primarily because of improved postoperative outcomes with refined tube stents and an improved visibility and accuracy of dacryoendoscopes 14 , 15 . The ENDI procedure is conducted while directly observing the obstructed site in the lacrimal duct using a dacryoendoscope and observing the nasal cavity using a nasal endoscope (Supplementary file, Video 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…With the increasing use of the dacryoendoscope and advances in the beroptic system, the use of the dacryoendoscope in diagnosing lacrimal out ow obstruction is also increasing. 12 The diagnosis and treatment of lacrimal out ow obstructions using the dacryoendoscope have remarkably increased over the past two decades particularly in East Asia, including Japan, Korea, and the Philippines. [13][14][15][16] East Asians have relatively at facial features, with a less elevated superior orbital rim than other ethnic groups, which may allow relatively easy manipulation of a dacryoendoscope.…”
Section: Introductionmentioning
confidence: 99%